a b + c + b c + a + c a + b = ?
If a + b + c = 6 and a 1 + b 1 + c 1 = 2 , find the value of the expression above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Awesome solution! Another similar approach is to use the fact that b + c = 6 − a and so on, at which point the expression simply becomes a 6 + b 6 + c 6 − 3 = 6 ⋅ 2 − 3 = 9 .
Log in to reply
That's what I did.
Also my strat
Is there any other method????
Log in to reply
Gj, did the same, but it's pretty easy so no big deal
a + b + c = 6
a 1 + b 1 + c 1 = 2
Notice that each denominator has the other 2 variables as the nominator, that would be achievable only by multiplication
So multiply the first 2 equations
( a + b + c ) × ( a 1 + b 1 + c 1 ) = ( 6 × 2 )
a a + b b + c c + a b + c + b a + c + c a + b = 1 2
a b + c + b a + c + c a + b = 1 2 − 3 = 9
It's so simple
It's also how i do it
We are given that a+b+c=6. So, a + b + c 1 = 6 1 . Another information we are given is a 1 + b 1 + c 1 = 2 . Relating these two, we can say that a + b + c 1 2 = a 1 + b 1 + c 1 , that is, a + b + c 1 2 = a b c b c + a c + a b . 1 2 a b c = ( a + b + c ) ( b c + a c + a b ) . 1 2 a b c = a b c + a 2 c + a 2 b + b 2 c + a b c + a b 2 + b c 2 + a c 2 + a b c . 1 2 a b c = a 2 ( b + c ) + b 2 ( a + c ) + c 2 ( a + b ) + 3 a b c . a 2 ( b + c ) + b 2 ( a + c ) + c 2 ( a + b ) = 9 a b c . a b c a 2 ( b + c ) + b 2 ( a + c ) + c 2 ( a + b ) = 9 . a b + c + b a + c + c a + b = 9 .
We can assume a, b, c to be the sides of a triangle since its logical that a, b, c are positive. Now make use of semi-perimeter of a triangle.
Multiplying the two given equations then simplifying. You'll get the answer. PROMISE.
a ┼ b ┼ c = 6
1/a ┼ 1/b ┼ 1/c = 2
(b┼c)/a ┼ (c┼a)/b ┼ (a┼b)/c = ?
b/a ┼ c/a ┼ c/b ┼ a/b ┼ a/c ┼ b/c
├ (a ┼b ┼c)/a - 1 ┼ (a ┼b ┼c)/b - 1 ┼ (a ┼b ┼c)/c- 1
├ 6/a - 1 ┼ 6/b - 1 ┼ 6/c - 1
├ 6 × (1/a ┼ 1/b ┼ 1/c) - 3
6 × (2) -3 = 9
Write (a+b+c-a)/a as first term, =(6/a)-1. Expn becomes 6(E(1/a)-3. E(1/a) is given as 2.E stands for sigma. Hence answer is 9.
Problem Loading...
Note Loading...
Set Loading...
First note that it is safe to assume that none of a , b , c equal 0 . Now let the given expression be S . Then we have that
S + 3 = S + a a + b b + c c = ( a b + c + a a ) + ( b c + a + b b ) + ( c a + b + c c ) =
a a + b + c + b a + b + c + c a + b + c = ( a + b + c ) ( a 1 + b 1 + c 1 ) = 6 × 2 = 1 2 .
Thus S + 3 = 1 2 , and so S = 9 .